2013
DOI: 10.1227/01.neu.0000430766.80102.ac
|View full text |Cite
|
Sign up to set email alerts
|

Chronic 30-Hz Deep Cerebellar Stimulation Coupled With Training Enhances Post-ischemia Motor Recovery and Peri-infarct Synaptophysin Expression in Rodents

Abstract: These results indicate that chronic activation of ascending cerebellofugal pathways enhances motor recovery after focal cortical ischemia. The recovery was associated with an increase in perilesional cortical plasticity relative to nontreated controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 21 publications
2
47
0
Order By: Relevance
“…Placement of deep cerebellar electrodes and focal ischemia were conducted as detailed previously (Baker et al, 2010;Machado et al, 2013). Briefly, animals were anesthetized with ketamine (50 mg/kg) and medetomidine (0.5 mg/kg) and fixed in a stereotaxic frame (David Kopf Instruments).…”
Section: Ischemia and Electrode Implantationmentioning
confidence: 99%
See 3 more Smart Citations
“…Placement of deep cerebellar electrodes and focal ischemia were conducted as detailed previously (Baker et al, 2010;Machado et al, 2013). Briefly, animals were anesthetized with ketamine (50 mg/kg) and medetomidine (0.5 mg/kg) and fixed in a stereotaxic frame (David Kopf Instruments).…”
Section: Ischemia and Electrode Implantationmentioning
confidence: 99%
“…Our group previously showed that motor rehabilitation associated with chronic stimulation of the dentatothalamocortical pathway is paralleled by greater expression of synaptophysin in immunohistochemistry ( Machado et al, 2013). In this experiment, the effects of stimulation on a family of proteins that play a key role in long-term potentiation (LTP) and synaptic plasticity were evaluated, namely synaptophysin, CaMKII, PSD95, and NMDAR1.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…By targeting it at its node of origin in the dentate nucleus or the ascending pathway, the majority of the tract can be activated with a single implanted multipolar electrode [69]. Invasive, subthreshold stimulation, delivered chronically at lower frequencies (in the beta range) can generate sustained facilitatory effects upon excitability of M1 [70] and promote recovery of the impaired forelimb to a significantly greater degree than in a control [71,72].…”
Section: Methodological: Targeting Peri-lesional Substrates Even Whilmentioning
confidence: 99%